Mediation Of Consumer Satisfaction On Product Quality And Quality Of Service To Customer Loyalty Hanamasa Restaurant In Jakarta - Rusiyati, Sri; Suleman, Dede; Zuniarti, Ida; Nurhayaty, Ety; Puspasari, Aprilia; Mustomi, Dede; Ariawan, Joko; Hakim, Lukman (IJOSMAS, 2022)
This study aims to analyze the mediating effect of customer satisfaction on product quality and service quality variables on customer loyalty at Hanamasa restaurant in Jakarta. Sampling used purposive sampling method, the collected data was processed using SmartPLS 3.0 software. The results showed that customer satisfaction was not significant as a mediating variable on the effect of product quality on loyalty, while on the effect of service quality on loyalty, customer satisfaction became a significant mediating variable. The findings of this study also show that service quality has a significant impact on customer satisfaction, and customer satisfaction has a significant impact on loyalty